Control of membrane biofouling by 6-gingerol analogs: Quorum sensing inhibition. (15th August 2019) - Ham, So-Young; Kim, Han-Shin; Jang, Yongsun; Sun, Peng-Fei; Park, Jeong-Hoon; Lee, John Seungwu; Byun, Youngjoo; Park, Hee-Deung
Graphical abstract: Highlights: 6-Gingerol analogs reduced biofilm formation without bacterial growth inhibition. 6-Gingerol analogs did not affect morphology and chemical structure of RO membranes. Permeate flux was increased by treatment of 6-gingerol analogs. 6-Gingerol analogs could control biofouling by regulating the expression of QS related genes. Abstract: Biofouling is a major problem in operating reverse osmosis (RO) processes. Although biocides such as chlorine are commonly used to reduce biofouling, their strong oxidative activity and toxicity negatively affect the operation of RO processes. 6-gingerol analogs, structural derivatives of the main component of ginger, are quorum sensing (QS) inhibitors. In this study, 6-gingerol analogs were applied to reduce biofouling in RO processes. The 6-gingerol analogs could inhibit Pseudomonas aeruginosa biofilm formation at low concentrations via QS disrupting activities without affecting the growth of the species. Notably, 6-gingerol analogs increased the permeate flux 36–52% in the operation of a model RO unit, with no damage to the membrane surface physically and chemically. Therefore, the results of this study clearly demonstrated that 6-gingerol analogs are effective biofilm inhibitors that could be used to mitigate biofouling in RO processes.